Third molar impaction - VE ADAMU; Chioma G. Okoye; Ndidiamaka Ijeoma F. Eneojo (Orapuh, Inc., 2021)
Third molar impaction is a pathological condition in which a 'wisdom tooth', which is the last permanent tooth to erupt in each quadrant of the oral cavity, lacks enough room to accommodate them and consequently fails to erupt or does not erupt properly. Third molar impaction presents with several oral and related health challenges. Early diagnosis and prompt and appropriate management will improve prognosis and prevent the associated complications. This review paper provides summarized information on the concept, aetiology, symptoms, effects, dangers, complications, diagnosis, and management of third molar impaction